Dieta del Macá Tobiano (Podiceps gallardoi) en el estuario del río Gallegos, Santa Cruz, Argentina - Torres, Eduardo R.; Vargas, Fabiana A. (Nuestras Aves, 2005)
Este artículo no cuenta con un resumen.